Customer Relationship Management Information System in Medika Lestari Hospitals - Tugiman Tugiman; Amat Basri; Benny Daniawan (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2020)
Marketing strategies based on efforts to create relationships between companies and customers are better known as Customer Relationship Management (CRM). CRM is a corporate strategy used to pamper customers so they don't look away. This study wants to find out and improve relations between hospitals and patients. Besides that, by building this system, can it affect customer / patient satisfaction. The quality of information systems is measured using the ISO 9126 model by adapting four characteristics of software quality: Functionality, Reliability, Usability, and Efficiency. The system development method uses the Rapid Application Development (RAD) model. Researchers will conduct system analysis and design using the Unified Model Language (UML), then coding with the PHP programming language and MySQL database, as well as collecting data using a questionnaire, and testing the system using the Blackbox Testing model. Based on testing using ISO 9126 the results are functionality (83%), Reliability (86%), Usability (87%), and Efficiency (83%). Overall the results are 85% (very good).